International Conference on Sustainable Infrastructure 2019 : Leading resilient communities through the 21st century : proceedings of the International Conference on Sustainable Infrastructure 2019 : November 6-9, 2019, Los Angeles, California - Chester, Mikhail Vin; Norton, Mark (Mark R.) (Engineer) (ASCE, American Society of Civil Engineers, 2019)
Proceedings of the International Conference on Sustainable Infrastructure 2019, held in Los Angeles, California, November 6-9, 2019. Sponsored by the Committee on Sustainability of ASCE. This collection contains 77 peer-reviewed papers on a broad array of contemporary issues in the development of sustainable infrastructure. Topics include: climate change; disruptive technologies; policy, finance, and management; education and practice; resiliency; society and urbanization; and case studies. This proceedings will be of interest to engineers, owners, construction managers, financial experts, technology developers, and government decision makers who work to create better, more integrated multi-beneficial projects.